Ethylene promotes germination of Arabidopsis seed under salinity by decreasing reactive oxygen species evidence for the involvement of nitric oxide simulated by sodium nitroprusside - Lin, Yingchao (Plant physiology and biochemistry : PPB, 2013)
Copyright © 2013 Elsevier Masson SAS. All rights reserved.